The Oldowan industry from Swartkrans cave, South Africa, and its relevance for the African Oldowan. Issue 123 (October 2018) - Kuman, Kathleen; Sutton, Morris B.; Pickering, Travis Rayne; Heaton, Jason L.
Abstract: The oldest recognized artifacts at the Swartkrans cave hominid-bearing site in South Africa have long been known to occur in the Lower Bank of Member 1, now dated with the cosmogenic nuclide burial method to ca. 1.8–2.19 Ma. However, the affinities of this industry have been debated due to small sample size. In this paper we present newly excavated material from the Lower Bank retrieved since 2005 in the Swartkrans Paleoanthropological Research Project. The sample is now large enough to confirm its affinity with the Oldowan industrial complex. The assemblage is highly expedient and core reduction strategies are largely casual. Although freehand flaking is present, the bipolar technique is most significant, even in non-quartz raw materials. The Swartkrans assemblage shows some significant contrasts with the Sterkfontein Oldowan, ca. 2.18 Ma, which can be explained by its closer proximity to raw material sources, its somewhat different geographic context, and its more expedient nature. The Swartkrans Oldowan now provides us with the first good indication of Oldowan variability in southern Africa, where only two sizeable assemblages have thus far been discovered. Comparisons are made with other sites across Africa that help to place this variability within our overall understanding of the Oldowan industrial complex.